Buenas Prácticas de Laboratorio (GLP) en el control de calidad de aguas - Silva Orozco, Talina (2008)
UCR::Docencia::Ciencias Agroalimentarias::Facultad de Ciencias Agroalimentarias::Escuela de Zootecnia